Desenvolvimento e avaliação de um ensaio imunoenzimático, usando antígeno multiepítopos, para o diagnóstico laboratorial da esquistossomose mansoni - Karine Ferreira Lopes (2020)
Intestinal schistosomiasis is a chronic disease, caused by the parasite Schistosoma mansoni, which still represents a serious public health problem in Brazil. The laboratory diagnosis of intestinal schistosomiasis, carried out by detecting parasite eggs in feces, has low sensitivity when applied to individuals with low parasitic load, which represents an obstacle for control and eradication of the disease. Serological tests can be more sensitive for the diagnosis of infection, especially when using recombinant antigens. These antigens can contain specific epitopes of one or more proteins, increasing the sensitivity and specificity of the test. Therefore, the objective of this work was to develop and evaluate an ELISA-based immunoenzymatic assay, using a multi-epitope antigen, produced with recombinant DNA technology. For this, the amino acid sequences of S. mansoni cathepsin B and asparaginyl endopeptidase were submitted for the prediction of B cell epitopes using the BepiPred 2.0 and the antigenicity prediction method described by Kolaskar & Tongaonkar, to select the peptide regions with higher antigenic potential. Together with peptide sequences obtained from previous works, these sequences were backtranslated into nucleotide sequences and used in the construction of a minigene. The minigene was inserted into plasmid pET28a and the construct was transformed into E. coli BL21 (DE3) pLysS, for large-scale production. After solubility analysis, the recombinant antigen was purified under denaturing conditions by nickel-sensitized resin affinity chromatography. Then, the antigen was renatured by means of dialysis against urea solutions in decreasing concentrations. This antigen was used to coat polystyrene microplates in an optimal concentration, previously determined by block titration against different dilutions of positive, negative control sera and anti-IgG-peroxidase conjugate, to standardize an ELISA assay, called ELISA IgG anti-SmME. The performance of the ELISA IgG anti-SmME was evaluated using sera from 118 positive and negative individuals for schistosomiasis. In addition, samples from individuals with other helminths were used. Subsequently, the assay was tested against serum samples from individuals before and three, six and twelve months after treatment with praziquantel, to assess the level of IgG antibodies in egg-negative and reinfected individuals. The cut-off point was defined by ROC (Receiver Operating Curve) analysis and the ELISA IgG anti-SmME resulted in a sensitivity of 68%, specificity of 66% and diagnostic accuracy of 67%. Most of the S. mansoni-infected individuals had a low parasitic burden. In their serum samples, the ELISA IgG anti-SmME showed 68% sensitivity for individuals with egg counts of ≤ 12 epg (eggs per gram feces) and 67% for individuals with 13-99 epg. In egg- positive individuals treated with praziquantel, no drop in antibody reactivity was observed, even up to 12 months after treatment. It is worth mentioning that, for the diagnosis of intestinal schistosomiasis, this was the first study using a multi-epitope recombinant antigen in an ELISA assay. It demonstrated applicability in the diagnosis of individuals with low parasitic load. In this sense, further work should be carried out to improve the performance of the ELISA IgG anti-SmME and make it an alternative for the laboratory diagnosis of schistosomiasis.